A comparative study on adding chopped kenaf fibers to the core of glass/epoxy laminates under quasi-static indentation: Experimental and numerical approaches. (October 2022) - Montazeri, Amin; Safarabadi, Majid
Implementation of natural fibers like kenaf in composite laminates has been the focus of many researchers. The considerable price of Low-Velocity Impact (LVI) testing, as well as the time constraints imposed by the short duration of this experiment, and prior reports of the obedience of Quasi-Static Indentation (QSI) test findings to LVI test results, have encouraged researchers to employ QSI instead of LVI. This work compares the mechanical characteristics of composite laminates consisting of chopped glass and kenaf fibers as a core and investigates the effect of hybridizing the mentioned chopped fibers as the core of a laminate. Three types of laminates with different core materials were fabricated to do this research. The results showed that among the laminates with the same weight, kenaf core laminate has the highest resistance against indentation and has the best performance in terms of absorbed energy, peak load, and damaged region. Using chopped kenaf fiber instead of chopped glass fiber can increase the absorbed energy and the peak load by 36% and 17%, respectively. Also, hybridizing the mentioned chopped fibers has not fully maximized the properties of the composite laminate during the QSI test. Finally, finite element modelling of the laminates was performed, and the numerical and experimental results were pretty aligned.